2013
DOI: 10.1021/ie401549w
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Direct Leaching of Natural Alunite in KOH

Abstract: Alunite is a potential resource for production of alumina and potassium sulfate.Hydrometallurgy is the conventional process employed for this purpose and direct leaching in KOH is suitable as one of the process steps because it does not require prior calcination. In this paper dissolution kinetics of pure natural alunite in KOH is described. Kinetics of dissolution of alunite in potassium hydroxide follows the shrinking core model. The rate of reaction is controlled by surface chemical reaction step and the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…The value of the activation energy (43.6 kJ mol À1 ) in eqn (9) for the alkaline leaching of olivine is in agreement with values obtained in previous studies of uid-solid reaction systems. 23,[37][38][39][40] For example, Abdel-Aal 37 described that, for a chemically controlled process, the value of the activation energy is usually greater than 41.84 kJ mol À1 . In most previous studies that have explored cheap and viable techniques to meet growing demand of APS, extraction of APS was achieved by acidic dissolution of olivine rocks.…”
Section: Kinetic Analysismentioning
confidence: 99%
“…The value of the activation energy (43.6 kJ mol À1 ) in eqn (9) for the alkaline leaching of olivine is in agreement with values obtained in previous studies of uid-solid reaction systems. 23,[37][38][39][40] For example, Abdel-Aal 37 described that, for a chemically controlled process, the value of the activation energy is usually greater than 41.84 kJ mol À1 . In most previous studies that have explored cheap and viable techniques to meet growing demand of APS, extraction of APS was achieved by acidic dissolution of olivine rocks.…”
Section: Kinetic Analysismentioning
confidence: 99%
“…One study investigated the hydrothermal conversion of sodium jarosite (NaFe 3 (SO 4 ) 2 (OH) 6 ), the byproduct of the zinc industry, to hematite using sulfuric acid at 225 °C and showed that the process requires 100% hematite seed addition and the optimum operating conditions are low free acid concentration (less than 0.5 M), temperature of 200–210 °C, and 1 h residence time. , Another study investigated the precipitation of hematite from chloride media via atmospheric acid leaching and showed that regardless of temperature, a minimum amount of hematite seed is required, and presence of impurities (CaCl 2 and NaCl) and higher initial HCl concentration decreases the product yield . One study investigated the kinetics of dissolution of alunite in KOH and determined that a temperature of 80 °C and 4 M concentration of KOH are optimum to completely dissolve alunite within a short period of time . There were also a few studies on the recovery of hematite from HPAL residue.…”
Section: Introductionmentioning
confidence: 99%
“…(15), plots of ln k vs. 1/T are shown in Fig. 9 process is the surface chemical reactions for Ni, Co, Mn and Li [25,35,42,50]. This is confirmed by the fact that the leaching rates of metals are influenced significantly by the leaching temperature, particularly at higher temperatures [42].…”
Section: Leaching Kinetics Analysismentioning
confidence: 65%
“…The leaching rate may be controlled by diffusion through a fluid film, the ash or product layer, or a surface chemical reaction [42]. As the shaking speed showed no effect on this reaction system, this implied that the diffusion through the fluid film was not the rate-controlling step in the leaching process [42,50].…”
Section: Leaching Kinetics Analysismentioning
confidence: 99%